Clinical experience and diagnostic algorithm of vulval Crohn's disease. Issue 7 (July 2017) - Boxhoorn, Lotte; Stoof, Tom J.; de Meij, Tim; Hoentjen, Frank; Oldenburg, Bas; Bouma, Gerd; Löwenberg, Mark; van Bodegraven, Adriaan A.; de Boer, Nanne K.H.
Abstract : Background and aim: Vulval Crohn's disease (VCD) is a rare extraintestinal cutaneous manifestation of Crohn's disease. No consensus on the diagnostic workup and therapeutic management of this condition has been provided in the current literature. Patients and methods: Retrospective, multicentre descriptive case series of female patients diagnosed and treated with VCD. By chart review, data on initial symptoms, clinical courses, histologic findings and therapeutic management were collected. Results: Fifteen female patients with a median age of 28 years (interquartile range: 28–44 years) suffering from Crohn's disease of the ileum (27%), colon (33%) and ileocolon (40%) were included. VCD manifested most frequently with vulval swelling (93%), pain (80%) and erythema (73%). Histologic analysis demonstrated granulomatous inflammation in 78% and a mixed inflammatory cell infiltrate in 67% of cases. In eight (53%) cases, topical therapy resulted in temporary reduction of vulval symptoms. Combotreatment with immunosuppressive agents and tumour necrosis factor α inhibitors was the most effective second-line therapy: five (33%) patients achieved sustained clinical remission with this therapeutic strategy. Conclusion: The diagnostic workup of VCD is challenging and should be approached in a multidisciplinary manner. Histopathologic analysis of the vulva supports the diagnosis. Topical therapy and systemic treatment with immunosuppressive agents and tumour necrosis factor α inhibitors are advised to treat this condition.